Pteridines CI Synthesis and Properties of Lumazine-6- and -7-carboxylic Acids - Eisele Roland; Aritomo Keiichi; Pfleiderer Wolfgang (Pteridines, 1993)
Lumazine-6-(8) and 7-carboxylic acid (23) and their N-methyl derivatives (12, 13, 21, 26, 28, 29) have been synthesized and characterized by the determination of their pK values and the UV spectra of the neutral, mono and dianion species. It was noticed that the acidities of the two N-H protons of the pyrimidine moiety are almost the same indicating that the dianions of 8 and 23, respectively, are I: 1 mixtures of the corresponding N-l and N-3 deprotonated forms. The lumazine-7-carboxylic acids (23, 26, 28, 29, 31, 33) are in comparison to their 6-carboxyJic acid counterparts (8, 12, 13, 21, 39) stronger acids by about I pK unit due to the resonance effect of the 4-oxo function on C-7 but not C-6. Alkaline KMn04 oxidation of 6.7-dimethyl-Iumazine (30) forms expectedly 6-methyl-Iumazine-7-carboxylic acid (31) in high yield according to the activation of the 7-methyl group by the electron-attracting 4-carbonyl residue.